2008
DOI: 10.1002/jbm.a.32137
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl‐cyanoacrylate is acutely nontoxic and provides sufficient bond strength for anastomosis of peripheral nerves

Abstract: Anastomosis is a common technique for the union of severed nerve trunks. This is commonly performed with sutures, a process that can be both time consuming and injurious to tissue. One promising alternative to suturing is the use of adhesives to join the severed segments. Cyanoacrylate-based glues have been used clinically as a surgical adhesive for soft tissues. However, the acute effects of these glues on nerve electrophysiology and the tensile strength of the rejoined tissues have not been evaluated. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 14 publications
1
12
0
Order By: Relevance
“…However, this can be avoided, by overlapping the adjacent epineural sheaths and using minimal amounts of glue (Fig. 1f) [12,72]. Choi et al reported that applying the cyanoacrylate glue in micro-drops to the outer epineurium on rat sciatic nerves reduced the compression effects, while providing adequate tensile strength to the nerve ends [12].…”
Section: Gluesmentioning
confidence: 97%
“…However, this can be avoided, by overlapping the adjacent epineural sheaths and using minimal amounts of glue (Fig. 1f) [12,72]. Choi et al reported that applying the cyanoacrylate glue in micro-drops to the outer epineurium on rat sciatic nerves reduced the compression effects, while providing adequate tensile strength to the nerve ends [12].…”
Section: Gluesmentioning
confidence: 97%
“…[19, 20] Interfacial strength of the tissue-adhesive specimens (Figs. 2a-b) was assessed by applying a constant displacement rate (0.05mm/s) normal to the tissue-adhesive-tissue interface (see Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…These results support the findings published in the literature, that cyanoacrylate glues can be used in direct contact with the nerve. [42][43][44][45][46] A dedicated experimentation is running to study the possible effect produced by a direct contact, inside the regeneration chamber, between the acrylate glue and the tiny regenerating axons and the associated Schwann's cells, even if this assembly is not expected to be ever encountered in a properly surgically implanted NeuroBox.…”
Section: Discussionmentioning
confidence: 99%